Myocardial hypoxic stress mediates functional cardiac extracellular vesicle release. (9th June 2021) - Anselmo, Achille; Frank, Derk; Papa, Laura; Viviani Anselmi, Chiara; Di Pasquale, Elisa; Mazzola, Marta; Panico, Cristina; Clemente, Francesca; Soldani, Cristiana; Pagiatakis, Christina; Hinkel, Rabea; Thalmann, Ruth; et al.
Abstract: Aims : Increased shedding of extracellular vesicles (EVs)—small, lipid bilayer-delimited particles with a role in paracrine signalling—has been associated with human pathologies, e.g. atherosclerosis, but whether this is true for cardiac diseases is unknown. Methods and results : Here, we used the surface antigen CD172a as a specific marker of cardiomyocyte (CM)-derived EVs; the CM origin of CD172a + EVs was supported by their content of cardiac-specific proteins and heart-enriched microRNAs. We found that patients with aortic stenosis, ischaemic heart disease, or cardiomyopathy had higher circulating CD172a + cardiac EV counts than did healthy subjects. Cellular stress was a major determinant of EV release from CMs, with hypoxia increasing shedding in in vitro and in vivo experiments. At the functional level, EVs isolated from the supernatant of CMs derived from human-induced pluripotent stem cells and cultured in a hypoxic atmosphere elicited a positive inotropic response in unstressed CMs, an effect we found to be dependent on an increase in the number of EVs expressing ceramide on their surface. Of potential clinical relevance, aortic stenosis patients with the highest counts of circulating cardiac CD172a + EVs had a more favourable prognosis for transcatheter aortic valve replacement than those with lower counts. Conclusion : We identified circulating CD172a + EVs as cardiac derived, showing their release and function and providing evidence for their prognostic potential in aortic stenosis patients. Graphical Abstract: